ENCOURAGING ACEHNESE EFL PROSPECTIVE TEACHERS IN REFLECTIVE PRACTICE - Wati, Shafrida (TELL - US JOURNAL, 2023)
Reflective teaching practice is an approach that promotes teachers' professional development. Experts emphasize that reflection does not occur naturally in most teachers, but it is a skill acquired through learning. Therefore, promoting the reflective practice in an early stage is pivotal. This research reports the implementation of reflective teaching strategies at an initial teacher education program in the context of Aceh. It further explores the impact of the learning on the student teachers’ practical teaching during an internship program. This study employed a qualitative inquiry for the research method. Observation and in-depth interviews were used as methods of data collection. The prospective teachers learned to reflect through several strategies; diary writing, dialogic lecturer’s feedback, recording lesson through video, and peer observation. The finding showed that the learning on reflection developed some student teachers' awareness to reflect in their teaching practice during the internship program. They assessed their strength and weaknesses in teaching by self-assessing during and after the learning took place, examining students’ involvement during classroom activities, asking students’ thoughts and feelings about the learning, and asking the supervisor’s feedback. Moreover, efforts they carried out to improve their teaching practice involved practicing teaching at home, finding out supporting materials, watching teaching videos on YouTube, and asking fellow novice teachers to conduct peer monitoring. The reflective teaching activities built their confidence in teaching, assisted them to deals with problems they encountered in real classrooms, and stimulated their creative ideas in facilitating the learning. Thus, reflective teaching practice is required to be embedded in initial teacher training curricula to generate reflective practitioners.